Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Huang, Qin-Cheng; Wang, Li; Gu, Zhi-Min; Liu, Cui; Ye, Tian-Tian; Yan, Jun-Jun; Meng, Ji-Lun; Zheng, Yu-Tong; Ge, Xian-Ping; Lin, Zhi-Deng; Zou, Guo-Yuan (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor (RXR), diacylglycerol acyltransferase 1 (dgat1) and carnitine palmitoyltransferase 1 (cpt1). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 (prx5) and improve immunity by upregulating expression of toll-like receptor 2 (toll2), myeloid differentiation factor 88 (myd88) and dosal in the hepatopancreas. The intestinal health related genes (crustin 2/3/4, anti-lipopolysaccharide factor 1/7, prx5, peritrophin-1, myosin light chain kinase, claudin, myd88 and dosal) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M. rosenbergii. To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.